The impact of indoor air quality and contaminants on respiratory health of older people living in long-term care residences in Porto - Mendes, A (2016)
BACKGROUND: persons who are 65 years or older often spend an important part of their lives indoors thus adverse indoor climate might influence their health status. OBJECTIVE: to evaluate the influence of indoor air quality and contaminants on older people's respiratory health. DESIGN: cross-sectional study. SETTING: 21 long-term care residences (LTC) in the city of Porto, Portugal. SUBJECTS: older people living in LTC with ≥65 years old. METHODS: the Portuguese version of BOLD questionnaire was administered by an interviewer to older residents able to participate (n = 143). Indoor air contaminants (IAC) were measured twice, during winter and summer in 135 areas. Mixed effects logistic regression models were used to study the association between the health questionnaire results and the monitored IAC, adjusted for age, smoking habits, gender and number of years living in the LTC. RESULTS: cough (23%) and sputum (12%) were the major respiratory symptoms, and allergic rhinitis (22%) the main self-reported illness. Overall particulate matter up to 2.5 micrometres in size median concentration was above the reference levels both in winter and summer seasons. Peak values of particulate matter up to 10 micrometres in size (PM10), total volatile organic compounds, carbon dioxide, bacteria and fungi exceeded the reference levels. Older people exposed to PM10 above the reference levels demonstrated higher odds of allergic rhinitis (OR = 2.9, 95% CI: 1.1-7.2). CONCLUSION: high levels of PM10 were associated with 3-fold odds of allergic rhinitis. No association was found between indoor air chemical and biological contaminants and respiratory symptoms.